2009
DOI: 10.4001/003.017.0211
|View full text |Cite
|
Sign up to set email alerts
|

Description of Four New Species ofDilytaFörster (Hymenoptera: Figitidae: Charipinae) from the Afrotropical Region

Abstract: Four new species of Dilyta (D. australafricana sp. n., D. ghanana sp. n., D. kenyana sp. n. and D. somaliana sp. n.) are described from the Afrotropical region, and the only previously known species of this genus from this region, D. africana (Benoit), is redescribed. These five species have two small apical carinae on the apex of the scutellum, instead of the ∩-shaped carina characteristic of the Dilyta species from the rest of the world. A key to the Afrotropical species of Dilyta and a checklist for all rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…2B), not meeting dorsally and thus not ∩ -shaped. This study, together with the other recent studies done with the genus Dilyta (Paretas-Martínez et al 2009;Ferrer-Suay et al in press), show that there is little interspecific morphological variability within the genus. The best characters to differentiate the species of Dilyta are the apex of scutellum ( fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2B), not meeting dorsally and thus not ∩ -shaped. This study, together with the other recent studies done with the genus Dilyta (Paretas-Martínez et al 2009;Ferrer-Suay et al in press), show that there is little interspecific morphological variability within the genus. The best characters to differentiate the species of Dilyta are the apex of scutellum ( fig.…”
Section: Discussionsupporting
confidence: 83%
“…Historically, one of the diagnostic characters assigned to Dilyta was the ∩ -shaped carina on the apex of the scutellum (Menke & Evenhuis 1991) ( fig. 2A), but Paretas-Martínez et al (2009) showed that this character is lacking in the Afrotropical species, which instead have only two small lateral symmetrical carinae ( fig. 2B), not meeting dorsally and thus not ∩ -shaped.…”
Section: Discussionmentioning
confidence: 99%
“…Endoparasitoids of Encyrtidae (Hymenoptera: Chalcidoidea) that are endoparasitoids of psyllids (Hemiptera: Psyllidae) (Fergusson 1986; Menke and Evenhuis 1991). Until now it has been cited in: Cacopsyllaalba , Cacopsyllapyricola , Psyllapyri , Psyllopsisfraxini by Menke and Evenhuis (1991: 152); Triozaerytreae by Paretas-Martínez et al (2009: 211) and Psyllidae on Firmianasimplex by Paretas-Martínez et al (2011: 34).…”
Section: Resultsmentioning
confidence: 99%
“…Afrotropical records: Cameroon (Lebel and Modesta 2007), Democratic Republic of Congo (Benoit 1956e), Botswana, Ghana, Kenya, Somalia, South Africa (Paretas-Martinez et al 2009), Madagascar (Pujade-Villar and Ferrer-Suay 2012), Rwanda, Zimbabwe (Ferrer-Suay et al 2013), Central African Republic, Nigeria, Tanzania, Uganda, Yemen (here).…”
Section: Figitidaementioning
confidence: 99%
“…Quinlan’s papers followed Nordlander’s (1982 and papers therein), providing the first treatment of Afrotropical cynipoids that employed phylogenetic considerations (Quinlan 1986, 1988). More recently there have been only smaller taxonomic group revisions: Ronquist (1995) on Liopteridae (worldwide); Allemand et al (2002) on Afrotropical Leptopilina ; Ros-Farré and Pujade-Villar (2006) on world Prosaspicera ; Liu et al (2007) on Paramblynotus ; Buffington and van Noort (2007) on Pycnostigminae; Buffington and van Noort (2009) on Anacharoides ; Nielsen and Buffington (2011) on Stentorceps ; Paretas-Martinez et al (2009) and Pujade-Villar and Ferrer-Suay (2012) on Afrotropical Dilyta ; Ferrer-Suay et al (2012, 2013) on Afrotropical Alloxysta ; or single taxa added Buffington (2010, 2012), Jimenez and Pujade-Villar (2008); Pujade-Villar (2012); and Mata-Casanova et al (2014). Buffington and van Noort (2012) and van Noort and Buffington (2013) treated the Afrotropical Liopteridae to the species level.…”
Section: Introductionmentioning
confidence: 99%